Video analysis of ex vivo beating hearts during preservation on the TransMedics® organ care system - Mendiola Pla, Michelle; Berrettoni, Silvia; Lee, Franklin H.; Rozzi, Giacomo; Marrano, Federica; Gross, Ryan T.; Evans, Amy; Wendell, David C.; Lezberg, Paul; Burattini, Margherita; Paolo lo Muzio, Francesco; Fassina, Lorenzo; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Reliable biomarkers for assessing the viability of the donor hearts undergoing ex vivo perfusion remain elusive. A unique feature of normothermic ex vivo perfusion on the TransMedics® Organ Care System (OCS™) is that the donor heart is maintained in a beating state throughout the preservation period. We applied a video algorithm for an in vivo assessment of cardiac kinematics, video kinematic evaluation (Vi.Ki.E.), to the donor hearts undergoing ex vivo perfusion on the OCS™ to assess the feasibility of applying this algorithm in this setting. Methods Healthy donor porcine hearts (n = 6) were procured from Yucatan pigs and underwent 2 h of normothermic ex vivo perfusion on the OCS™ device. During the preservation period, serial high-resolution videos were captured at 30 frames per second. Using Vi.Ki.E., we assessed the force, energy, contractility, and trajectory parameters of each heart. Results There were no significant changes in any of the measured parameters of the heart on the OCS™ device over time as judged by linear regression analysis. Importantly, there were no significant changes in contractility during the duration of the preservation period (time 0–30 min, 918 ± 430 px/s; time 31–60 min, 1,386 ± 603 px/s; time 61–90 min, 1,299 ± 617 px/s; time 91–120 min, 1,535 ± 728 px/s). Similarly, there were no significant changes in the force, energy, or trajectory parameters. Post-transplantation echocardiograms demonstrated robust contractility of each allograft. Conclusion Vi.Ki.E. assessment of the donor hearts undergoing ex vivo perfusion is feasible on the TransMedics OCS™, and we observed that the donor hearts maintain steady kinematic measurements throughout the duration.